RESPON PEMBERIAN PUPUK NPK 15.15.15 DAN PUPUK ORGANIK CAIR ELANG BIRU TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN CABAI (Capsicum annuum L.) VARIETAS CABAI MERAH KERITING - Gideon Permanto (UNIVERSITAS LABUHANBATU, 2019)
One factor that determines the quality of chili seeds is growing media fertility. Fertility of growing media can be improved by fertilization therefore, through the application of NPK 15.15.15 fertilizer and liquid organik fertilizer blue elbow is expected to increase the growth of pepper plants. The research design used was factorial randomized block design with two factors studied, the first factor was NPK 15.15.15 (N) and organik fertilizer liquid blue eagle (M) with 12 combinations. The treatment of NPK 15.15.15 is N0 = 0 gr / polybag, N1 = 10 gr / polybag, N2 = 20 g / polybag and N3 = 30 g / polybag, while the organik liquid liquefaction of blue eagle is M0 = 0 ml / l water, M1 = 2 ml / l water, M2 = 3 ml / l water. The observed parameters were plant height (cm), stem diameter (cm), flowering plant age (day), and sample plant grain weight (gr). The result of this research showed that NPK 15.15.15 fertilizer on red curly plants showed very significant effect on plant height and real to fruit weight but not significant on the age of stalk and stem diameter. The treatment of liquid organik fertilizer of blue eagle on plants showed significant differences in the age of neonrophytic flowering plants not significant in stem diameter, fruit weight, and plant height. The interaction between NPK 15.15.15 fertilizer and liquid organik fertilizer of blue eagle showed no significant difference in all parameters observed. Keywords: curly red pepper, NPK 15.15.15 fertilizer, liquid organik fertilizer.